Policies and their impacts in the mining area of North Konawe Regency - Milyan, Milyan; Kasmawati, Andi; Rifdan, Rifdan; Niswaty, Risma (Iapa Proceedings Conference, 2025)
This study aims to examine and analyze policies and their impacts in the mining area of North Konawe Regency, as well as examine the implications of mining policies and provide solutions for communities in the mining area of North Konawe Regency. This is a qualitative study using a phenomenological approach. Data was collected through interviews, observations, and documentation, then analyzed using triangulation methods and reduced until the data obtained was saturated and valid. The results of this study indicate that: (a) policy implementation, namely communication, resources, information and authority, disposition and bureaucratic structure, has been carried out by policy implementing agents. The communication process is carried out in a tripartite manner, and government authority is no longer in the regions since the enactment of Law No. 3 of 2020 concerning mining, so that local governments only supervise and control the media when conflicts occur. (b) the impact of government policies on the socio-economic conditions of the community has not had a significant impact. The existence of mining has not provided sufficient space to promote community welfare at a macro level, with challenges including ineffective implementation in the field, social conflict, and the impact of environmental damage.